A novel Cr3+-doped stannate far red phosphor for plant lighting: structure evolution, broad-narrow spectrum tuning and application prospect. (December 2022) - Gai, S.J.; Zhou, C.; Peng, L.; Wu, M.H.; Gao, P.X.; Su, L.J.; Molokeev, M.S.; Zhou, Z.; Xia, M.
Abstract: Chemical unit cosubstitution is an effective strategy to regulate the luminescence properties of phosphors, and it has attracted huge attention in the last few years. Following the design principles of the match of effective ion radius, atomic valence equilibrium and stoichiometric substitution, the local structure of crystal can be well customized, which is beneficial to develop high-performance luminescent materials. In this work, Mg 2+ -Sn 4+ sites were cosubstituted by Zn 2+ -Ti 4+ ion pairs in Mg2 SnO4 : Cr 3+, respectively, and the emission spectra was successfully serially tuned from broad-band to narrow-band along with a unique variation trend of blue shift first and then slightly red shift. The photoluminescence excitation (PLE), photoluminescence (PL) spectra, lifetime decay, Raman spectra and electron paramagnetic resonance (EPR) were used to analyze the mechanism of luminescence tuning. Based on the manipulation of local structure, the as-observed distinct luminescence tuning can be well understood by the crystal field theory, nephelauxetic effect and changed Cr 3+ capacity in this phosphor. Moreover, the adjusted narrow-band far-red emission spectra peak at 732 nm, matching the characteristic absorption of plant phytochrome PFR, has broad application prospects in the field of plant growth lighting. In addition, light-regulated dwarf potted tomato experiments were carried out to verify the application of far-red light in plant growth. Graphical abstract: Structure evolution, spectral tuning, device applications and quality improvement. Image 1 Highlights: The emission spectra of phosphor Mg2 SnO4 :Cr 3+ were successfully tuned (754 ∼ 716 nm) to meet the requirements of phytochrome absorption spectra. The mechanism of emission spectrum tuning is discussed. The spectral similarity between the photopigment and the obtained phosphor was evaluated. Light regulation experiments of dwarf-potted tomato were carried out to verify the effect of far-red light on plant growth.